Quantification of neocortical ratios in stem primates. Issue 3 (18th February 2015) - Long, Adam; Bloch, Jonathan I.; Silcox, Mary T.
ABSTRACT Extant euprimates (=crown primates) have a characteristically expanded neocortical region of the brain relative to that of other mammals, but the timing of that expansion in their evolutionary history is poorly resolved. Examination of anatomical landmarks on fossil endocasts of Eocene euprimates suggests that significant neocortical expansion relative to contemporaneous mammals was already underway. Here, we provide quantitative estimates of neocorticalization in stem primates (plesiadapiforms) relevant to the question of whether relative neocortical expansion was uniquely characteristic of the crown primate radiation. Ratios of neocortex to endocast surface areas were calculated for plesiadapiforms using measurements from virtual endocasts of the paromomyid Ignacius graybullianus (early Eocene, Wyoming) and the microsyopid Microsyops annectens (middle Eocene, Wyoming). These data are similar to a published estimate for the plesiadapid, Plesiadapis tricuspidens, but contrast with those calculated for early Tertiary euprimates in being within the 95% confidence intervals for archaic mammals generally. Interpretation of these values is complicated by the paucity of sampled endocasts for older stem primates and euarchontogliran outgroups, as well as by a combination of effects related to temporal trends, allometry, and taxon‐unique specializations. Regardless, these results are consistent with the hypothesis that a shift in brain organization occurred in the first euprimates, likely in association with elaborations to the visual system. Am J Phys Anthropol 157:363–373, 2015. © 2015 Wiley Periodicals, Inc.